2018
DOI: 10.1038/s41375-018-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent 8q24 rearrangement in blastic plasmacytoid dendritic cell neoplasm: association with immunoblastoid cytomorphology, MYC expression, and drug response

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare skin-tropic hematological malignancy of uncertain pathogenesis and poor prognosis. We examined 118 BPDCN cases for cytomorphology, MYC locus rearrangement, and MYC expression. Sixty-two (53%) and 41 (35%) cases showed the classic and immunoblastoid cytomorphology, respectively. Forty-one (38%) MYCBPDCN (positive for rearrangement and expression) and 59 (54%) MYCBPDCN (both negative) cases were identified. Immunoblastoid cytomorphology was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 49 publications
2
53
0
2
Order By: Relevance
“…1c). Notably, a recent study reported that 22 out of 118 BPDCN patients harbored t(6;8) and enhanced expression of MYC, compared to BPDCN cells without t(6;8) 8 . Therefore, the expression of MYC are increased in BPDCN cells harboring t(6;8).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1c). Notably, a recent study reported that 22 out of 118 BPDCN patients harbored t(6;8) and enhanced expression of MYC, compared to BPDCN cells without t(6;8) 8 . Therefore, the expression of MYC are increased in BPDCN cells harboring t(6;8).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…TP53 and CDKN2A ), and loss-of-function mutations in epigenetic modifiers (e.g. TET2 ) 4 , which are commonly mutated in myeloid malignancies 5 , whereas chromosomal translocation (6;8)(p21;q24) was exclusively observed in patients with BPDCN 68 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that historically, the relationship between the nucleolus and cancer has been discussed because the number and shape of nucleoli are altered in almost any type of cancer cell. An enlarged and prominent nucleolus is one of the indicators of cancer diagnoses in histopathology (Montanaro et al 2008;Sakamoto et al 2018). Such a phenomenon might indicate that a cancerspecific nuclear environment affects or induces the function and assembly/disassembly of condensates inside cancer cells.…”
Section: The Formation and Regulation Of Membrane-less Cellular Organmentioning
confidence: 99%
“…2 For example, changes in composition, number, size and activity on nucleoli are seen, and their diagnostic significance has been proposed 47,48 The prominent nucleolus observed in a rare hematological malignancy, blastic plasmacytoid dendritic cell neoplasm, is a compelling case. 49 Another relevant alteration is found in the PML body, in which the level of SUMOylation may underlie LLPS. 50 In acute promyelocytic leukemia (APL), heterozygotic chromo-…”
Section: Nucle Ar Microenvironments Are Altered In C An Cer Smentioning
confidence: 99%